2018
DOI: 10.1590/s2175-97902018000217459
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity study of a polysaccharide based hydrogel from linseed for potential use in drug delivery system

Abstract: Linseed hydrogel (LSH) was evaluated by acute toxicity for its potential application in oral drug delivery design. White albino mice and rabbits were divided in four groups (I-IV) and different doses of LSH (1, 2 and 5 g/kg body weight) were given except to the control group (I) that was left untreated. Rabbits were monitored for eye irritation, acute dermal toxicity and primary dermal irritation, whereas, body weight, food and water consumption, hematology and clinical biochemistry, gross necropsy and histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Liver lobules of group B were present with clear dividing lines, similar to group A. No hypertrophy was obvious on hepatic sinusoid and no neutrophil, lymphocyte, or macrophage infiltration was observed, indicating lack of any toxicity (Haseeb et al, 2018). Spleen sinus was absolutely normal, without any evidence of toxicity or pathological alteration in both control and hydrogel treated group.…”
Section: Histopathological Studymentioning
confidence: 65%
“…Liver lobules of group B were present with clear dividing lines, similar to group A. No hypertrophy was obvious on hepatic sinusoid and no neutrophil, lymphocyte, or macrophage infiltration was observed, indicating lack of any toxicity (Haseeb et al, 2018). Spleen sinus was absolutely normal, without any evidence of toxicity or pathological alteration in both control and hydrogel treated group.…”
Section: Histopathological Studymentioning
confidence: 65%
“…The lack of a vital dissimilarity in liver enzymes level displays the protective hepatotoxic state, and absence of significant differences in creatinine and urea also demonstrate the nephroprotective property of QSM-co-AAm hydrogels on the health of rabbits. The complete blood, renal, liver and lipid profiles were similar to the control group and appeared in normal range, which demonstrated safety profile of QSM-co-AAm hydrogels [ 31 ].…”
Section: Discussionmentioning
confidence: 90%
“…The results of the hematology and biochemical analysis of the control and test group rabbits are shown in Table 5. The complete analysis of the blood indicates that all the values were found within a normal range [81]. Moreover, as shown in Figure 11, histopathological studies revealed no significant alterations or abnormality in the tissue structures of the rabbits treated with hydrogel when compared with the control groups [82].…”
Section: Acute Oral Toxicity Studymentioning
confidence: 82%
“…The results of the hematology and biochemical analysis of the control and test group rabbits are shown in Table 5. The complete analysis of the blood indicates that all the values were found within a normal range [81].…”
Section: Acute Oral Toxicity Studymentioning
confidence: 94%